2016
DOI: 10.1080/03008207.2016.1187141
|View full text |Cite
|
Sign up to set email alerts
|

In vivo structural and cellular remodeling of engineered bone–ligament–bone constructs used for anterior cruciate ligament reconstruction in sheep

Abstract: Anterior cruciate ligament (ACL) ruptures rank among the most prevalent and costly sports-related injuries. Current tendon grafts used for ACL reconstruction are limited by suboptimal biomechanical properties. We have addressed these issues by engineering multiphasic bone-ligament-bone (BLB) constructs which develop structural and mechanical properties similar to native ACL. The purpose of this study was to examine the acute remodeling process that occurs as the BLB grafts advance toward the adult ligament phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The implantation of cells has been shown to profoundly influence the regenerative outcome via complex and intertwined mechanisms involving the release of biochemical cues, the in vivo deposition of ECM, and the formation of a template to recruit progenitor cells . A recent insight into the biological events leading to tissue regeneration using cell sheets for ACL regeneration has been provided in an ovine model . This study showed a significant remodeling of the cell sheet in the early period of the implantation, featuring a cell death peak at 3 d post implantation concomitant with an increase in neutrophil infiltration followed by collagen densification at a later stage, consistent with tissue maturation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The implantation of cells has been shown to profoundly influence the regenerative outcome via complex and intertwined mechanisms involving the release of biochemical cues, the in vivo deposition of ECM, and the formation of a template to recruit progenitor cells . A recent insight into the biological events leading to tissue regeneration using cell sheets for ACL regeneration has been provided in an ovine model . This study showed a significant remodeling of the cell sheet in the early period of the implantation, featuring a cell death peak at 3 d post implantation concomitant with an increase in neutrophil infiltration followed by collagen densification at a later stage, consistent with tissue maturation.…”
Section: Discussionmentioning
confidence: 81%
“…This study showed a significant remodeling of the cell sheet in the early period of the implantation, featuring a cell death peak at 3 d post implantation concomitant with an increase in neutrophil infiltration followed by collagen densification at a later stage, consistent with tissue maturation. In addition, the presence of implanted cells gradually diminished in the tissue engineered graft while the total cell number increased at 28 d post surgery suggesting infiltration of new cells at this more advanced healing stage . This indicates that the cells participated actively in both the recruitment of host cells and the creation of a suitable ECM template necessary for graft maturation and healing to take place.…”
Section: Discussionmentioning
confidence: 96%
“…There is no standard large animal model for nerve repair studies, but a number of species are used in other disciplines. The ovine animal model is established as a standard surgery model regarding orthopedic questions to investigate treatment options in arthrosis, osteoarthritis or damage of cruciate ligaments [ 57 59 ]. Porcine animals are predominantly used in trauma and intensive care research [ 60 – 62 ] and feline models are used as ear, nose and throat (ENT) surgical standard models [ 63 ].…”
Section: Current Experimental Approaches In Peripheral Nerve Reconstrmentioning
confidence: 99%
“…After 6 months in vivo, repair of a torn rotator cuff tendon with an ETG‐RC showed a significant increase in collagen alignment at the enthesis compared to suture‐only repaired tendons. Previous work in our sheep ACL studies indicate that the constructs are being decellularized during the early stages of remodeling and ultimately may serve as a scaffold for the infiltrating host cells . The histological analysis of the tendon‐to‐bone interface of suture‐only repairs was characterized by a layer of poorly organized, cellular, fibrovascular tissue with no evidence of a native‐like enthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in recovery time may account for the differences in gap length. Additionally, previous work using our technology in five sheep ACL studies indicate that at least a 6‐month recovery and up to 2 years is necessary to yield more optimal outcomes …”
Section: Discussionmentioning
confidence: 99%